Community-Acquired Clostridium difficile Diarrhea Caused by Binary Toxin, Toxin A, and Toxin B Gene-Positive Isolates in Hungary - Terhes, Gabriella (American Society for Microbiology, 2004)
The aim of this work was to study the toxin types of Clostridium difficile isolates originating from different parts of Hungary. A PCR method was used for amplification of the two major toxin genes and the binary toxin gene and to detect the deletion or insertion in the 3′ end of the toxin A gene. The findings were compared with the results of cytotoxicity assays on the HeLa cell line. One hundred twelve isolates were tested; the toxin A and toxin B genes were detected in 79 strains by the PCR method. All of the isolates that were positive by the PCR method were also positive by the cytotoxicity assay. All of the other strains (n = 33) were negative for the toxin A and toxin B genes; in these cases, cytopathic effects on the cell line were not observed. No tcdA-negative and tcdB-positive isolates were found by the PCR method. In two cases, the presence of a binary toxin gene was observed by PCR; both isolates that were isolated from diarrheal feces carried the tcdA and tcdB genes. No prior hospitalization had occurred in either case.